Movement difficulties in children with ADHD: Comparing the long‐ and short‐form Bruininks–Oseretsky Test of Motor Proficiency—Second Edition (BOT‐2). (16th January 2020) - Mancini, Vincent; Rudaizky, Daniel; Howlett, Sarah; Elizabeth‐Price, Jordan; Chen, Wai
Abstract: Aims: Up to 50% of children with attention deficit hyperactivity disorder (ADHD) also present with difficulties with motor proficiency. Several assessments of motor proficiency are available for occupational therapists, though the validity of these measures in an ADHD population requires further exploration. The aim of this paper was to evaluate the consistency of scores obtained using the long‐form and short‐form of the Bruininks–Oseretsky Test of Motor Proficiency—Second Edition (BOT‐2) in a school‐age ADHD sample. Method: The BOT‐2 long‐form was administered to 84 school‐age children (78 males) with ADHD; short‐form scores were extracted from the relevant long‐form items. Results: Long‐form and short‐form total scores were highly correlated ( r = .87), though the average short‐form score was significantly higher. As a categorical measure, 52 children were classified as "at‐risk" for movement difficulties by the long‐form; but only 36 by the short‐form, yielding a false‐negative rate of 30.77%. The sensitivity of short‐form could be improved by raising the cut‐off thresholds of short‐form scores as identified by receiver operating characteristic curve analysis but did not yield practical utility. Interpretation: As a continuous indicator (i.e. total scores), the short‐form is comparable to the long‐form. However, the short‐form overestimates the child's motor proficiency relative to the long‐form and yields an unacceptably high rate of false negatives as a categorical measure. The current revision of the short‐form is therefore not recommended as a screening nor diagnostic instrument in an ADHD population. In the absence of ADHD‐specific norms, use of the long‐form provides greater opportunity for occupational therapists to identify those at‐risk for movement difficulties. However, any assessment of motor proficiency should be accompanied by a broader comprehensive assessment to best understand a child's motor functioning.